Analysis the Effect of Profitability, Current Ratio, and Ownership Structure on Firm Value - Mahrus, Dede Muhamad; Mariana, Khofifa Mezza; Ramadhini, Sarah; Rawi, Rawi (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: This study aims to analyze the effect of profitability, current ratio and ownership structure on firm value and dividend policy as moderation, in manufacturing sector companies listed on the Indonesia Stock Exchange during the period 2020-2023. Design/methodology/approach: This research uses an associative method approach and the analysis uses multiple liner regression analysis and moderation regression analysis (MRA). Findings: Profitability, current ratio and ownership structure have a positive effect on firm value. As for the results of the MRA test analysis that dividend policy can moderate profitability, current ratio, and ownership structure affect firm value. Paper type: Research paper.